Cybercrimes and Economic Crisis in Nigeria: Essentialising Containment Beyond the Rhetoric - Emmanuel U. Awak (International Journal on Economics, Finance and Sustainable Development, 2022)
Just as the emergence of Internet and ICT innovates, instigates and transforms all facets of life and sectors of the society; so also, is the tenacity, tempo and geometric penetration of cybercrimes. The devastating consequences including economic doldrum, low gross domestic product (GDP), inclement investment environment, loss of billions and confidence through e-fraud, e-scams, data interception, and system and data interference, among others beckon decisive inhibition. However, slow and ill-implementation of legislation, lack of virtual evidence, knowledge of investigation and parochialism has continued to define most actions to protect the cyberspace. The paper qualitatively through social survey and multi-stage sampling methods examines parameters of cybercrimes as one of the enablers of economic crisis in Nigeria, using Akwa Ibom State as a specific study site. The discourse is shaped within theoretical frame of Situational Crime Prevention (SCP), since its strands are descriptive of the ravaging circumstances of cybercrimes, cybercriminals, and the obtuse and ductile tactics toward containment of cybercrimes. The result indicates that cybercrimes have strangulated the economy, and that its prevalence and spate annihilate germane quest for economic recovery. Therefore, utilisation of data surveillance technologies, SCP intervention techniques, cybercrimes’ awareness and education, intelligence-policing, faithful legislation and implementation are recommended.